Influence of high-intensity interval training and intermittent fasting on myocardium apoptosis pathway and cardiac morphology of healthy rats - Carvalho, Marianna R.; Mendonça, Maria Lua M.; Oliveira, Jéssica M.L.; Romanenghi, Rodrigo B.; Morais, Camila S.; Ota, Gabriel E.; Lima, Aline R.R. [UNESP]; Oliveira, Rodrigo J.; Filiú, Wander F.O.; Okoshi, Katashi [UNESP]; Okoshi, Marina P. [UNESP]; Oliveira-Junior, Silvio A.; et al. (Elsevier, 2021)
Aim: To evaluate the influence of intermittent fasting and high-intensity interval training (HIIT) on myocardial apoptosis signaling and cardiac morphological characteristics in healthy rats. Methods: Male Wistar rats (n = 60) were divided into four groups: sedentary control (SED-C), intermittent fasting (SED-IF), high-intensity interval training (HIIT-C), and high-intensity interval training plus intermittent fasting (HIIT-IF). SED-C and HIIT-C groups were treated daily with ad libitum chow; SED-IF and HIIT-IF received the same standard chow every other day. HIIT-C and HIIT-IF rats were submitted to an HIIT protocol five times a week for 12 weeks. At the end of the experiment, functional capacity, cardiac morphology, and expression of apoptosis signaling pathways-related proteins were analyzed. Key findings: HIIT increased cardiomyocyte cross-sectional area, collagen interstitial fraction, and the pro-apoptotic proteins AIF and caspase-3 expression, and reduced pro-apoptotic protein CYTC expression and the cleaved-to-non-cleaved PARP-1 ratio in myocardium. Intermittent fasting reduced cardiomyocyte cross-sectional area, collagen interstitial fraction, and expression of Bax, CYTC and cleaved PARP-1, and increased expression of the anti-apoptotic protein BCL-2. SMAC, ARC, and caspase-8 expression was not changed by HIIT or intermittent fasting. Significance: HIIT promotes cardiomyocyte hypertrophy and interstitial fibrosis, and modulates the apoptosis signaling pathway in healthy rat myocardium. Intermittent fasting reduces pro-apoptotic and increases antiapoptotic signaling, besides attenuating HIIT-induced cardiomyocyte hypertrophy and myocardial interstitial fibrosis.
Keywords: Apoptosis; Heart; Physical exercise; Time restricted feeding